PEMBERDAYAAN UMKM BERBASIS PELATIHAN DAN PENDAMPINGAN AKUNTANSI SEDERHANA DALAM MENINGKATKAN PENGELOLAAN KEUANGAN USAHA DI DESA MARUBUN JAYA - Indah Cahyani Pramesti Nasution; Yusmalinda Yusmalinda (Jurnal Ilmiah Akuntansi, 2026)
Micro, Small, and, Medium Enterprises (MSMEs) play an important role in supporting the rural economy; however, many MSME actors have not yet implemented regular and systematic financial record-keeping. Common problems include the absence of separation between personal and business finances, inconsistent transction recording, andlimited understanding of simple financial statements such as income statements and inventory records. This community service activity aimsto improve MSMEs’ financial management through training and assistance in simple accounting record-keeping in Marubun Jaya Village method used was direct assistance to 13 MSMEs through several stages, including initial sociailization, basic financial management training, daily  transaction recording practice, preparation of simple income statement, inventory recording, as well as monitoring and evaluation. The result show an improvement in MSMEs’ understanding and skills in simple income statements, and managing separate personal and business finances and became more orderly in financial adminitration. Therefore, simple accouting assistance hasproven to have positive impact on improving financial literacy and supporting MSME bussiness management in Marubun Jaya Village.